Catalogue raisonné as memoir : a composer's life - Argento, Dominick (University of Minnesota Press, 2004)
Each chapter of this memoir is based on a composition, surrounded by Dominick Argento's reflections on the period in his life when the piece was written and its opening performance. In a lifetime of compositions, Argento has encouraged audiences to focus on their own hopes and fears. Now he shares his own, illuminating the nature of music and its hold on the imagination.